Accelerating drug development for neuroblastoma - New Drug Development Strategy: an Innovative Therapies for Children with Cancer, European Network for Cancer Research in Children and Adolescents and International Society of Paediatric Oncology Europe Neuroblastoma project. (3rd August 2017) - Moreno, Lucas; Caron, Hubert; Geoerger, Birgit; Eggert, Angelika; Schleiermacher, Gudrun; Brock, Penelope; Valteau-Couanet, Dominique; Chesler, Louis; Schulte, Johannes H; De Preter, Katleen; Molenaar, Jan; Schramm, Alexander; et al.
ABSTRACT: Introduction : Neuroblastoma, the commonest paediatric extra-cranial tumour, remains a leading cause of death from cancer in children. There is an urgent need to develop new drugs to improve cure rates and reduce long-term toxicity and to incorporate molecularly targeted therapies into treatment. Many potential drugs are becoming available, but have to be prioritised for clinical trials due to the relatively small numbers of patients. Areas covered : The current drug development model has been slow, associated with significant attrition, and few new drugs have been developed for neuroblastoma. The Neuroblastoma New Drug Development Strategy (NDDS) has: 1) established a group with expertise in drug development; 2) prioritised targets and drugs according to tumour biology (target expression, dependency, pre-clinical data; potential combinations; biomarkers), identifying as priority targets ALK, MEK, CDK4/6, MDM2, MYCN (druggable by BET bromodomain, aurora kinase, mTORC1/2) BIRC5 and checkpoint kinase 1; 3) promoted clinical trials with target-prioritised drugs. Drugs showing activity can be rapidly transitioned via parallel randomised trials into front-line studies. Expert opinion : The Neuroblastoma NDDS is based on the premise that optimal drug development is reliant on knowledge of tumour biology and prioritisation. This approach will accelerate neuroblastoma drug development and other poor prognosis childhood malignancies.